Minimizing the economic unit cost of dragline-truck-shovel operations at Yatagan-Eskihisar open pit mine, Turkey - C. O. Aksoy (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
There is a long history of coal production in Turkey with electric energy generated from power plants since the 1950s. However, the cost of power generation is high. Therefore, it has become necessary to find a means of decreasing production costs to become more competitive in a global market. This paper attempts to economically minimize the overall operating costs of a dragline-shovel-truck system applied at an open pit mine that has fed the Yatagan power plant since 1979, lowering the lignite production cost, and indirectly, the overall electricity generation unit cost. Systems currently in place, as a result of former optimization studies, are time-consuming and expensive to re-implement to comply with today’s very different geometric and economic conditions affecting mining operations. In such cases, rather than re-optimization, it is more viable to identify the parameters that affect the minimum unit cost, via a cost minimization study, allowing present mine equipment to be utilized more efficiently. Unit cost minimization analyses are subject to the capacity of the pool of mining equipment available, combined with the mining block geometry from pre-stripping onwards. In this overall unit cost minimization study, P&H shovels and CAT 777 trucks with capacities of 15 yd3 and 77 tons, respectively, were used in truck-shovel pre-stripping operations. A 65 yd3 Marion 8050 dragline was used to expose the overburden immediately over the coal seam. Pre-stripping bench heights varied from 8 m to 20 m and dragline bench heights from 20 m and 25 m were evaluated to minimize the unit cost of field operations. Total overburden extended to a depth of 60 m (35 m to 40 m for pre-stripping). Minimization analyses performed on the pre-stripping truck-shovel operation, prior to dragline operations, determined that the shovel bench height should be 15 m requiring a dragline bench height of 25 m.